A case study of the role of higher order thinking skills on the development of sight reading ability for piano beginners at age seven to ten / Siow Lian Cheng - Siow, Lian Cheng (2015)
To access towards the effectiveness of higher order thinking skills towards children’s sight-reading ability improvement individually, this study used qualitative observations and a qualitative analysis of sight-reading ability improvement, upon four young piano beginners, with age, 7, 8, 9, and 10. The four subjects in this study were selected based on their distinct behaviors and distinct sight-reading abilities. All students participate in seventh week of sight-reading lessons, which the first week was a pretest of sight-reading before proceeding towards the first lesson in the second week, and the seventh week was a posttest of sight-reading after a period of five-week sight-reading lessons associated with higher order thinking skills. This qualitative case study was determined to observe the following issues through the sight-reading tests and lessons: a) students’ commitment during the lessons, and manipulation of the lesson materials, b) role of higher order thinking skills and thinking techniques of the sightreading lesson contents, c) the contribution of higher order thinking skills towards the students’ sight-reading experience, and d) comparison of students’ sight-reading improvement before and after the lesson period. Researcher chose to conduct the research in case study form due to the importance of reveal the bits and details of how thinking skills play role in the whole process of teaching and learning, and how students’ gain benefits towards their sight-reading ability. The data collection was based upon the observation towards the video recording of each session, of each four students, focusing upon each subjects sight-reading performance and behavioral performance during their participation in the lessons.